2020
DOI: 10.3390/plants9091245
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Air Temperatures and Its Effects on Growth and Productivity of Tomato in South Florida

Abstract: Florida ranks first among US states in fresh-market tomato production with annual production exceeding one-third of the total annual production in the country. Although tomato is a signature crop in Florida, current and future ambient temperatures could impose a major production challenge, especially during the fall growing season. This problem is increasingly becoming an important concern among tomato growers in south Florida, but studies addressing these concerns have not been conducted until now. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…For the first time in the Czech Republic, the genetic coefficient for this specific variety of tomato, different parameters like anthesis date, crop maturity date, harvest yield, total biomass weight, maximum LAI were incorporated into the DSSAT crop model. In a recent study, Ayankojo and Morgan (2020) also observed similar ranges of FL-SH, EM-FL and FL-SD in cultivar file for Florida 47 cultivar of tomato. This finding was consistent with Scholberg et al .…”
Section: Discussionmentioning
confidence: 55%
“…For the first time in the Czech Republic, the genetic coefficient for this specific variety of tomato, different parameters like anthesis date, crop maturity date, harvest yield, total biomass weight, maximum LAI were incorporated into the DSSAT crop model. In a recent study, Ayankojo and Morgan (2020) also observed similar ranges of FL-SH, EM-FL and FL-SD in cultivar file for Florida 47 cultivar of tomato. This finding was consistent with Scholberg et al .…”
Section: Discussionmentioning
confidence: 55%
“…In terms of yield, no significant differences were observed among the treatments, which could be caused in part for the differences in climatic conditions recorded under the different treatments, as protected cultivation regardless of the net color showed much higher temperatures and much lower relative humidity percentage compared to open field conditions. Previous studies have shown how an increase in temperatures could result in heat stress for tomato, evidenced as detrimental effects on fertility rate, flower drop, reduced fruit setting and in consequence reduce fruit production and lower yields [26][27][28]. Therefore, and although plants under colored shade conditions yielded taller plants, with larger leaves, the higher temperature recorded under this light condition may prevent the plants from achieving their full potential yield compared to conventional and open field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Johkan et al,(2011) also depicted that during the time of flowering, higher temperature results in abscission of flowers, very poor flowering and low fruit quality, pollen sterility and low color development in tomato. It was also observed that an increase of coldness or hotness in the South Florida has lower fruit numbers and yield of tomatoes, with little pollen viability and fruit set and the continuous rise in temperature could further reduce the productivity (Ayankojo and Morgan, 2020). The increase of rainfall and high relative humidity are also destructive to tomato plants, as the proliferation of leaf diseases is higher during the period of humid conditions (Kalibbala, 2011).…”
Section: Impact Of Climate Change On Tomato Productionmentioning
confidence: 99%